2018
DOI: 10.1002/ags3.12199
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates in perioperative chemotherapy and recurrence pattern of gastric cancer

Abstract: Gastrectomy with D2 lymph node dissection has become the global standard procedure for locally advanced gastric cancer to maximally reduce locoregional recurrence. In East Asia, based on the evidence of the ACTS‐GC and the CLASSIC trials, postadjuvant chemotherapy with S‐1 monotherapy or capecitabine and oxaliplatin after curative D2 gastrectomy is the current standard strategy. However, approximately 20% to 30% of patients still develop distant recurrence even after these postadjuvant chemotherapies, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
(40 reference statements)
0
17
0
2
Order By: Relevance
“…Based on the results of the previous pivotal randomized phase III trials, adjuvant chemotherapy is usually performed after surgery, in order to circulate the anticancer drug(s) throughout the entire body via the bloodstream to control micrometastases and prevent recurrence [4,25,26]. Although postoperative adjuvant chemotherapy is effective in the survival of patients with locally advanced gastric cancer, approximately 20-30% of patients still develop recurrence [19][20][21][22][23][24][25][26][27][28]. The results of the Adjuvant Chemotherapy Trial of S-1 for Gastric Cancer (ACTS-GC) showed the median time from recurrence to death for recurrent gastric cancer patients was 11.4 months [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the previous pivotal randomized phase III trials, adjuvant chemotherapy is usually performed after surgery, in order to circulate the anticancer drug(s) throughout the entire body via the bloodstream to control micrometastases and prevent recurrence [4,25,26]. Although postoperative adjuvant chemotherapy is effective in the survival of patients with locally advanced gastric cancer, approximately 20-30% of patients still develop recurrence [19][20][21][22][23][24][25][26][27][28]. The results of the Adjuvant Chemotherapy Trial of S-1 for Gastric Cancer (ACTS-GC) showed the median time from recurrence to death for recurrent gastric cancer patients was 11.4 months [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…8 A number of studies have shown that postoperative adjuvant therapy is an important factor in reducing local recurrence rate and improving survival. 9–11…”
Section: Discussionmentioning
confidence: 99%
“…FOCUS (IdentifierNCT01364376) is an ongoing trial comparing the efficiency of SOX versus FOLFOX in a neoadjuvant setting. RESOLVE 2 (Identifier NCT03691454) and MATCH (Identifier NCT02725424) are ongoing trial investigating the efficacy of SOX versus DOS with/without trastuzumab in a neoadjuvant setting [26].…”
Section: The Preoperative Neoadjuvant Settingmentioning
confidence: 99%